Production of target cathodes from composite silicides for applying protective coatings using casting and deformation technologies - I. A. Ivanov; A. G. Slutsky; V. A. Scheinert; A. I. Ivanov; A. N. Bely (Литьë и металлургия, 2021)
The article discusses the results of manufacturing multicomponent consumable cathodes of vacuum electric arc evaporation plants. To obtain ingots of complex silicide as a raw material for the manufacture of target cathodes, it is proposed to use induction melting of pure metal charge materials in an argon atmosphere.The method made it possible to obtain ingots of complex silicide with a composition close to the calculated one and a density of at least 93 %. Further forming of the cathode takes place when controlling the powder fractions by their percentage ratio with a pressing force of at least 50 tons. The results obtained are compared with the SHS method of manufacturing cathodes of identical composition.